STRATEGI KOMUNIKASI EFEKTIF DALAM MENINGKATKAN PELAYANAN KESEHATAN GUNA MEMBANGUN CITRA DAN REPUTASI DIMASYARAKAT: Studi kasus Puskesmas rawat inap Ketapang - Madiniah, Sa’adatul; Nulhaq, Pangeran Arsyad Ihsan (Komsospol, 2022)
Puskesmas is an important entity in the health system in Indonesia. Community health centers have a crucial role in providing basic health services to local communities. A good image and reputation act as key factors in influencing public trust and participation in health programs. This research uses a qualitative descriptive method with a case study of the Ketapang inpatient health center. The data obtained in this research was obtained through interviews, observation and analysis of related articles. This research aims to find out the strategies used by the community health center to improve communication in serving patients. Effective communication and good service will certainly have an impact on the image and reputation of the health center. From the results of an interview with one of the management staff at the puskesmas, it was clear that communication between medical personnel and patients was quite good and effective, such as when medical personnel carried out examinations, they provided diagnoses and explanations of patient complaints well, so that patients could understand the disease they were complaining about. Apart from that, every medical personnel must also understand therapeutic communication, which is very important so that communication between medical personnel and patients can run well and get appropriate feedback.